Asymmetric European summer heat predictability from wet and dry southern winters and springs (2012)
The mega heatwaves that struck western Europe in 2003 (ref. 1) and Russia in 2010 (ref. 2) are thought to provide a foretaste of future European summer climate3,4,5,6,7. Our ability to anticipate such events remains poor8, limiting adequate society adaptation. A deficit of precipitation in the preceding months favours summer heatwaves9,10,11,12,13, but the potential predictability from spring surface-moisture deficits, addressed in only a few case studies8,14,15, largely remains to be investigated. By analysing 64 years of observed temperature and precipitation we show that rainy winter/spring seasons over southern Europe inhibit hot summer days whereas dry seasons are followed by either a high or a low frequency of hot days, generalizing findings obtained over southeastern Europe10. Observations indicate that summer heat is more sensitive to the occurrence of specific weather regimes in initially dry cases than wet cases, inducing this asymmetry in summer heat predictability. Then, simulations from the Coupled Model Intercomparison Project (ref. 16 and J-L., Dufresne, manuscript in preparation) indicate that projected drier conditions over southern Europe are likely to induce a widening in the frequency distribution of hot summer days, as the wet winter/spring seasons are likely to become rare. These mechanisms are found to play an increasingly important role in coming decades, with more hot extremes and a modified hot-day predictability.